The Intimate Partner Flooding Scale. (September 2020) - Foran, Heather M.; Lorber, Michael; Malik, Jill; Heyman, Richard E.; Slep, Amy M. Smith
Dysfunctional conflict resolution behaviors in couples have been long recognized as markers of relationship maladjustment and are, consequently, frequent targets of couple therapy. The process of flooding may play a role. Flooding is the subjective sense of being overwhelmed by the partner's negative affect, which is perceived as unexpected and intense, and feeling as though one's information processing is impaired. It has been theorized that flooding is so aversive as to lead to maladaptive conflict behaviors (e.g., conflict escalation or withdrawal) as attempts to terminate the offending input (i.e., partner anger). Despite strong theory describing the construct, there has been a lack of valid measures to assess it. In the present study, we evaluated the psychometric properties of a 15-item measure in a sample of 453 couples. Reasonable unifactoriality, excellent internal consistency, and high test–retest reliability were demonstrated. Furthermore, using a dyadic latent variable model, the IPFS showed strong structural validity and concurrent validity with measures of relationship satisfaction, intimate partner violence, anger, depressive symptoms, and observed negative conflict behaviors. The IPFS appears to be a promising, economical instrument to assess flooding, a process relevant for understanding dysfunctional couple conflict behaviors.